Financial integration between sukuk and bond indices of emerging markets:insights from wavelet coherence and multivariate-GARCH analysis - Bhuiyan, Rubaiyat Ahsan; Rahman, Maya Puspa; Saiti, Buerhan; Mat Ghani, Gairuzazmi (Borsa Istanbul Anonim Sirketi, 2018)
Some investors strive for capital appreciation while others may follow capital preservation strategies in terms of investment. In relation to that, Islamic finance receives a lot of attention from institutional investors and asset managers in the search for higher returns, lower correlation and growth potentiality. Therefore, it would be meaningful to investigate whether sukuk can offer any advantage in terms of global diversification. In such context, we have examined the volatilities and correlations of bond indices of emerging counties such as South Korea, Singapore, China, India, Indonesia, and Malaysia with Thomson Reuters BPA Malaysia Sukuk Index by applying wavelet coherence and Multivariate GARCH analyses. The data covers the period January 2010 to December 2015. We conclude that the sukuk market offers effective portfolio diversification opportunities for fixed income investors of the mentioned sample countries. Global and regional investors can avail the benefits of portfolio diversification through investment in sukuk markets but portfolio diversification is not feasible domestically. As a practical implication to the finance industry, the outcome of this research provides a framework for investigating sukuk market integration of several emerging bond markets which serve as an important platform for conducting further research.